Sporothrix schenckii and sporotrichosis - Lopes-Bezerra,Leila M. (2006)
For a long time sporotrichosis has been regarded to have a low incidence in Brazil; however, recent studies demonstrate that not only the number of reported cases but also the incidence of more severe or atypical clinical forms of the disease are increasing. Recent data indicate that these more severe forms occur in about 10% of patients with confirmed diagnosis. The less frequent forms, mainly osteoarticular sporotrichosis, might be associated both with patient immunodepression and zoonotic transmission of the disease. The extracutaneous form and the atypical forms are a challenge to a newly developed serological test, introduced as an auxiliary tool for the diagnosis of unusual clinical forms of sporotrichosis.